Capturing the Students’ Voices on Technology-Based Assessment in English for Journalism - Lu'luil Maknun; Valentina Dyah Arum Sari; Restu Arini (LPPM Universitas Bumigora Mataram, 2026)
In the digital era, language assessment is increasingly shaped by technology; however, limited attention has been given to how students experience technology-based assessment, particularly in the English for Journalism context. This study aims to examine students’ perspectives on the implementation of technology-based assessment in an English for Journalism course, with a focus on integrating Assessment for Learning (AfL), Assessment as Learning (AaL), and Assessment of Learning (AoL). Using a qualitative descriptive method, data were collected through semi-structured interviews with 25 undergraduate students in 14 instructional meetings. Various digital tools were utilized, including Google Forms and Mentimeter for AfL, Google Classroom and Moodle for AoL, and reflective activities for AaL. The findings reveal that technology-based assessments fostered engagement, motivation, and self-regulation, leading students to become more reflective and autonomous in their learning. Moreover, authentic journalism-oriented tasks supported the development of professional identity and communicative competence. However, students also reported challenges, including inconsistent internet connectivity, digital fatigue, and a need for more timely and dialogic feedback. Overall, the study demonstrates that integrating AfL, AaL, and AoL through digital platforms transforms assessment into an interactive, learner-centered process. The study contributes to current discourse on technology-mediated assessment in English for Specific Purposes (ESP) by emphasizing the pedagogical value of listening to learners’ perspectives. Recommendations and implications for future research are also provided to enhance assessment literacy and the integration of sustainable technologies in language education.